Molecular and immunological characterization of Mus a 5 allergen from banana fruit - Aleksic, I.; Popovic, M.; Dimitrijevic, R.; Andjelkovic, U.; Vassilopoulou, E.; Sinaniotis, A.; Atanaskovic-Markovic, M.; Lindner, B.; Petersen, A.; Papadopoulos, N. G.; Gavrovic-Jankulovic, M. (Mol Nutr Food Res, 2012)
Banana fruit has become an important cause of fruit allergy in the recent years. Among the five registered IUIS allergens, Mus a 1 and Mus a 2 have been characterized in detail. In this study, molecular characterization and evaluation of the allergenic properties of β-1,3-glucanase from banana (Musa acuminata), denoted as Mus a 5, were performed.|The gene of Mus a 5 was cloned and sequenced. The obtained cDNA revealed a novel Mus a 5 isoform with an open reading frame encoding a protein of 340 amino acids comprising a putative signal peptide of 28 amino acid residues. By MALDI-TOF analysis Mus a 5 isolated from banana fruit revealed a molecular mass of 33451±67 Da. Two Mus a 5 isoforms (pI 7.7 and 8.0) were detected by 2D immunoblot with an identical N-terminal sequence. By mass fingerprint, 76 and 83% of the primary structure was confirmed for the two mature Mus a 5 isoforms, respectively. IgE reactivity to Mus a 5 was found in 74% of patients sensitized to banana fruit. Upregulation of basophil activation markers CD63 and CD203c was achieved with Mus a 5 in a concentration-dependent manner.|Mus a 5 is a functional allergen and a candidate for the component-resolved allergy diagnosis of banana allergy.
Keywords: 3(4)-beta-Glucanase Female Food Hypersensitivity Fruit Humans Immunoglobulin E Male Molecular Sequence Data Musa Phosphoric Diester Hydrolases Plant Proteins Protein Isoforms Pyrophosphatases Skin Tests Up-Regulation Young Adult; Adolescent Adult Allergens Amino Acid Sequence Antigens; CD63 Antigens; Molecular Endo-1; Plant Cloning